Al-‘Alāqah bayn al-Dīn wa al-Dawlah bi Indūnīsiyā: Tan Malaka wa Ārā’uhu al-Siyāsīyah - Azhar, Khairil (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
The present article is about the relation between religion and state as it is discussed by a prominent figure whose contributions to Indonesian politic are out of question. He is Tan Malaka, who has been considered as a radical Marxist activist. Through his works, including Madilog: Materialisme, Dialektika, Logika; Islam dalam Tinjauan Madilog Dari Penjara ke Penjara; Naar De Republiek Indonesie; Tan Malaka shows his deep appreciation to Marxism. That is why, in these works, be pays a great attention to liberation movement and freedom for people both from colonial domination and from feudalism rooted in Indonesian culture.DOI: 10.15408/sdi.v7i2.711